HUBUNGAN PENGUASAAN TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) GURU TERHADAP MOTIVASI GURU DALAM PENGGUNAAN TEKNOLOGI DALAM PEMBELAJARAN DI SEKOLAH DASAR - Wiguna, Arya Chandra; Budiman, Nandang; Sardin (Universitas Muhammadiyah Surakarta, 2024)
This study aims to analyze the relationship between Technological Pedagogical Content Knowledge (TPACK) competence and teachers' motivation to use technology in elementary school teaching. A quantitative approach with a correlational design was employed, involving 47 teachers selected through purposive sampling. Descriptive analysis revealed that the average TPACK competence score of teachers was 45.87 (categorized as moderate to high) with a standard deviation of 5.597, while the average motivation score was 51.04 with a standard deviation of 5.967. Pearson correlation analysis indicated a very strong positive relationship between TPACK and teachers' motivation (r = 0.857, p = 0.000). These findings suggest that better TPACK competence enhances teachers' motivation to utilize technology in teaching. The implications of this study highlight the need for continuous training and institutional support to improve teachers' TPACK competence, which in turn can promote broader technology adoption in elementary education.